2020
DOI: 10.1021/acsami.0c05636
|View full text |Cite
|
Sign up to set email alerts
|

Self-Powered and Broadband Lead-Free Inorganic Perovskite Photodetector with High Stability

Abstract: Metal halide perovskite materials have opened up a great opportunity for high-performance optoelectronic devices owing to their extraordinary optoelectronic properties. More than lead halide ones, stable and nontoxic bismuth halide perovskites exhibit more promise in their future commercialization. In this work, we developed for the first time photodetectors based on full-inorganic Cs 3 Bi 2 I 9−x Br x perovskites and modulate their performance by varying x in the composition systematically. Among those self-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
79
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 46 publications
(95 reference statements)
3
79
0
Order By: Relevance
“…[ 47 ] Therefore, our photodetectors featuring MBI films grown through 2T‐CVD surpass the environmental stability of all other bismuth‐based PIM photodetectors reported in the literature (Table 1). [ 46–50 ] The cutting‐edge stability of 2T‐CVD photodetectors may be traced to the uniform, compact and smooth films produced with the 2T‐CVD approach, consistent with our previous findings from lead‐halide perovskite devices. [ 23,24,33,56–61 ] In fact, grain boundaries in polycrystalline films have often been linked to the degradation of perovskite/perovskite‐inspired materials in a humid environment.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…[ 47 ] Therefore, our photodetectors featuring MBI films grown through 2T‐CVD surpass the environmental stability of all other bismuth‐based PIM photodetectors reported in the literature (Table 1). [ 46–50 ] The cutting‐edge stability of 2T‐CVD photodetectors may be traced to the uniform, compact and smooth films produced with the 2T‐CVD approach, consistent with our previous findings from lead‐halide perovskite devices. [ 23,24,33,56–61 ] In fact, grain boundaries in polycrystalline films have often been linked to the degradation of perovskite/perovskite‐inspired materials in a humid environment.…”
Section: Resultssupporting
confidence: 87%
“…[ 46 ] Additionally, all devices based on inorganic double perovskites have similar responsivity, but two orders of magnitude lower detectivity compared with our devices. [ 15,45–50 ] Consequently, the devices reported in the present study exhibited superior figures of merit ( R and D *) while operating in self‐powered mode.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…We found that the dissociation rate of the Fe(NH 4 ) 2 (SO 4 ) 2 salt is relatively slow, which promotes high‐aspect‐ratio film growth as a stabilizing effect, consistent with the density functional theory (DFT) calculations. In addition to its good durability, the unencapsulated FeBHT device exhibited the highest air stability reported so far for self‐powered photodetectors equipped with organic–inorganic hybrid photoabsorbers (Figure S2a , Supporting Information) [ 31 , 32 , 33 ] and was comparable to all‐inorganic systems (Figure S2b , Supporting Information); [ 34 , 35 , 36 , 37 , 38 , 39 ] 94% of the photocurrent is retained after 60 days of exposure to air, which implies that the organometallic 2D nanosheets used in the laboratory research can be used in actual optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…To address these problems, tremendous efforts have been made to replace Pb 2+ with other environmentally friendly metal cations, such as Sn 2+ , Bi 3+ , Cu 2+ , Sb 3+ , and Ge 2+ . [ 18–26 ] The corresponding devices (solar cells, light emissions, etc.) have achieved many great breakthroughs.…”
Section: Introductionmentioning
confidence: 99%